The relationship between archaeological interventions and local identity: A comparative study between students from the districts of Supe Puerto and Paramonga. Barranca, Perú - Postigo Echaiz, Wilmer Eduardo (2023)
This comparative study analyzes the relationship between archaeological interventions in the districts of Supe Puerto and Paramonga, located in the province of Barranca, department of Lima, anda the identity formation of their respective secondary school student groups. To understand this relationship, semi-structured interviews were conducted with the students, information on archaeological interventions in general was reviewed, and the most representative archaeological sites of each district were visited. Results of this study showed that there is a relative difference in the construction of identity between the study groups of each district, which is understood bye the current situation of the archaeological sites anda the specific social interaction that occurs in the context of archaeological practice.